Solvent extraction of nickel(II) from sulphate solution using capric acid - SLIMANI, A.; BARKAT, D. jddama (Science des matériaux (Laboratoire LARHYSS), 2015)
In this work we have studied the extraction of nickel(II) from a sulphate medium with capric acid noted (HA) in chloroform at 25°C in this study we will try to understand the behavior of this metal by varying a set of parameters like pH , the extractant concentration, polarity of solvent, effect of temperature on the extraction of this metal was also discussed. stoïchiometry of extracted species in the organic phase is NiR2(HR)2 , the equilibrium constants have been evaluated as well as thermodyn